2017
DOI: 10.1520/jte20150171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Foot Protection Effectiveness Against AP Mine Blasts: Effect of Deflector Geometry

Abstract: In this study, the effectiveness of blast deflectors used in protective footwear against antipersonnel (AP) mines was investigated. The tip angle of a V-shaped deflector and the overall shape (symmetrical, unsymmetrical) were chosen as the design parameters to be examined, whereas parameters such as deflector material and wall thickness were kept constant. Both explicit dynamic finite element analysis (LS-Dyna) and blast tests were performed to evaluate the effectiveness of these design parameters. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A deflector which was used at the mentioned samples consists of 2 mm-thick steel plates and the inner parts were filled with 3 mm aluminum honey comb core. 21 The top of the deflector was covered with a cover which consists of a 1 mm thick steel plate after placing the honeycomb inside the deflector. The deflector was placed on the boot's heel.…”
Section: Sole and Protective Boots Designmentioning
confidence: 99%
“…A deflector which was used at the mentioned samples consists of 2 mm-thick steel plates and the inner parts were filled with 3 mm aluminum honey comb core. 21 The top of the deflector was covered with a cover which consists of a 1 mm thick steel plate after placing the honeycomb inside the deflector. The deflector was placed on the boot's heel.…”
Section: Sole and Protective Boots Designmentioning
confidence: 99%
“…Because there is not any reinforcing or energy absorbing material in standard military boot soles, the effects of the blast were transmitted directly to the tibia axis. Previous studies 14,20 found that deformable composite structures should be used for effective energy absorption. The energy absorption properties of the type-2 and type-3 samples that were used in previous experiments had been studied in detailed using a mechanical leg model.…”
Section: Strain Gauge Resultsmentioning
confidence: 99%
“…The deflectors, which were used in the mentioned samples, consist of 2-mm-thick steel plates, and the inner parts were filled aluminum honeycomb cores with 3-mm cells. 14 The top of the deflector was covered with a 1-mm-thick steel plate after placing honeycomb inside the deflector. The deflector was placed on the heels of the boots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation